(untitled) (Nóema, 2015)
The problems of the philosophy of language, of the explanation and understanding, of the translation andinterpretation of texts,stand at the forefront ofthe philosophical works of the great theoretician from the field of phenomenological hermeneutics Paul Ricœur. The philosopher takes the opportunity to present his viewpoint on these issues in the book On Translation, which is precisely concerned with the problems recounted above. Thevolume consists of three essays written in the 1990s: «Translation as Challenge and Source of Happiness», «The Paradigm of Translation», «A Passage: Translating the Untranslatable». The authorhimself is experienced in translation, having produced a French version of the principal work of E. Husserl Ideas, Volume 1 while imprisoned in Germany during World War II. Unlike a simplereproduction of a text in a different language, for Ricœur translation is a mission topromotea cultural dialogue,a mission that demandsfrom the translator readiness to «immerse into the foreign language»and an aptitude for «linguistic sensitivity».